PENGARUH PENGUASAAN LITERASI DIGITAL MAHASISWA TERHADAP INSTIKI E-LIBRARY - Paramarta, Krisna Adi; Suhartika, I Putu; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 3 No 2 (2023), 2023)
This study aims to determine the effect of student digital literacy mastery on the use of the INSTKI ELibrary. This study uses a descriptive quantitative method approach. Quantitative is a process to find knowledge by using data in the form of numbers as a tool to find information. Research data obtained from primary data and secondary data. Data analysis techniques in this study used validity tests, reliability tests, descriptive data analysis and simple linear regression analysis using SPSS (Statistical Package Social Science) software. The results of this study state that there is a significant influence between Student Digital Literacy Mastery on the Utilization of the INSTKI E-Library.